Bullying and learning disruption in high school students in Chilpancingo, Mexico (Revista Innova Educación, 2020)
Given the wave of violence in the state of Guerrero, Mexico, it is important to know the effects of this phenomenon on the behavior and academic performance of adolescent students. Likewise, it is necessary to inquire the causes in which the most common violent behaviors manifest themselves, as well as to postulate local and institutional alternatives that improve school care for this highly vulnerable population in the face of organized crime. Having said this, the purpose of this work is to investigate the constitutive elements that generate bullying and disruption of learning in the students of Technical Secondary No. 185 Hermenegildo Galeana in the city of Chilpancingo. For this, qualitative ethnographic work was carried out in order to explain in a dense and detailed way the power relations between students, as well as the conditions in which the teaching-learning process develops. In the same way, we rely on questionnaires, surveys and interviews to better deepen the purpose of this research.
Keywords: Learning; bullying; education; school; violence